“Breast is best”… until they say so - Quinones, Cristina (Frontiers in Sociology, 2023)
In this autoethnographic paper, I discuss the consequences of being exposed to two competing breastfeeding discourses during my first mothering experience; the “self-regulated dyad” and the “externally regulated dyad” discourse. The former represents the ideal scenario, and the evidence-based practices recommended by the World Health Organisation (i.e., breastfeeding on demand, internally regulated by the dyad). The externally regulated discourse refers to the standardized health interventions that take over when difficulties arise (e.g. weight gain deviations, latching issues). Building on Kugelmann’s critique about our blind reliance on “standardized health”, existing evidence, and my own breastfeeding journey; I argue that unqualified, unindividualized breastfeeding interventions are highly counterproductive. To illustrate these points, I discuss the implications of the polarized interpretation of pain and the limited dyadically focused support. I then move on to analyse how ambivalent social positioning around breastfeeding impacts our experience. In particular, I found that I was highly regarded as a “good, responsible mum” up till my baby was 6 months, and how breastfeeding became increasingly challenged when my daughter was approaching her first birthday. Here, I discuss how performing attachment mothering identity work allowed me to navigate these challenges. Against this backdrop, I reflect upon feminist ambivalent positionings on breastfeeding and the complexity of balancing the promotion of women’s hard earned rights whilst supporting them to engage in whatever baby feeding choice they feel appropriate. I conclude that unless we acknowledge the physical and social complexities of the process, and our healthcare systems seriously invest in allocating human resources and training them appropriately, breastfeeding rates may continue to suffer and women continue to interiorize it as their own failure.